Connecting Distributed Version Control Systems communities to linked open data - Aslan, Khaled; Skaf-Molli, Hala; Molli, Pascal (2012 International Conference on Collaboration Technologies and Systems, 2012)
Distributed Version Control Systems (DVCS) such as Git or Mercurial allow community of developers to coordinate and maintain well known software such as Linux operating system or Firefox web browser. The Push-Pull-Clone (PPC) collaboration model used in DVCS generates PPC social network where DVCS repositories are linked by push/pull relations. Unfortunately, DVCS tools poorly interoperate and are not navigable. The first issue prevents the development of generic tools and the second one prevents network analysis. In this paper, we propose to reuse semantic web technologies to transform any DVCS system into a social semantic web one. To achieve this objective, we propose SCHO+ a lightweight ontology that allows to represent causal history sharing. This ontology allows each node of the PPC social network to publish semantic datasets. Next, these semantic datasets can be queried with link transversal based query execution for metrics computation and PPC social network discovery. We experimented PPC network discovery and divergence metrics on real data from some representative projects managed by different DVCS tools.